Customer Generated Content sebagai Faktor Pembentuk Kepercayaan Konsumen pada Merek Digital Shopee: Studi pada Pengguna Shopee di Kabupaten Jombang - Masruchan Masruchan; Iwan Adinugroho; La Ode Muhamad Arifin (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to examine the effect of customer-generated content (CGC) on consumer trust in the digital brand Shopee, with perceived information credibility as a mediating variable. A quantitative explanatory approach was employed, involving 120 Shopee users in Kabupaten Jombang selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). CGC in this study includes written reviews, ratings, comments, as well as user-generated photos and videos shared within the platform. The results indicate that customer-generated content has a positive effect on perceived information credibility and directly enhances consumer trust. In addition, perceived information credibility is found to partially mediate the relationship between CGC and consumer trust. This finding suggests that consumer trust is not only influenced by the volume of user-generated content but also by its perceived accuracy, objectivity, relevance, and authenticity. In other words, the quality and credibility of information embedded in CGC play a central role in shaping users’ trust toward the platform.The study implies that Shopee and its sellers should encourage the creation of authentic, informative, and verified user content to strengthen consumer trust and improve overall marketplace engagement. These results provide practical insights for digital marketing strategies in local e-commerce environments and highlight the importance of managing user-generated content as a key trust-building mechanism.